Kajian Mengenai Kegiatan Verifikasi Lapangan Atas Pengenaan Bea Perolehan Hak Atas Tanah Dan Bangunan (BPHTB) - Dedeh Diarti (Otentik's : Jurnal Hukum Kenotariatan, 2019)
Fee for acquisition of right of land and building (BPHTB) is a central tax that diverted into the local tax as provided in Law No. 28 of 2009. For BPHTB collection purpose, local government shall establish regional regulation concerning BPHTB. Based on that, then the Bogor Government issued Law No. 15 of 2010 on BPHTB. The collection of BPHTB, since 2011, was transferred to Local Revenue Office of Bogor. For such collection, then the office also issued a regulatioan on field verification of land and building subjected to collection of BPHTB. Field Verification aims to examine the correctness and to investigate the validity of tax object and documents received with actual field condition, especially on matters relating to the sale price of the land and building which are transacted.